The Unbearable Fear of Psi: On Scientific Censorship in the 21st Century - Cardeña, Etzel (Journal of Scientific Exploration, 2015)
In this paper, I describe various examples of blatant attempts to censor parapsychology research and those doing it. They include raising false accusations, suppressing papers and data, and ostracizing scientists interested in the topic. The intensity of fear and vituperation caused by parapsychology research is disproportionate even to the possibility that the psi hypothesis could be completely wrong, so I speculate on psychological reasons that may give rise to it. There are very few circumstances in which censorship might be appropriate, and the actions by parapsychology censors put them at odds not only with the history of science but with the history of modern liberal societies. An appendix includes an editorial censored by the then-editors of the Journal of Human Neuroscience.